Empirical Analysis of the Factors Affecting FTA Utilization by Exporting SMEs: Evidence from the South Korean Textile Industry - Joon-heon Song (East Asian Economic Review (EAER), 2022)
Despite the proliferation of free trade agreements (FTAs), many exporting firms are still confronted with several challenges in utilizing the FTA preferential tariffs. Based on the Technology–Organization–Environment (TOE) framework, this study empirically examines the factors affecting the utilization of FTA schemes by exporting firms. To clarify the key factors influencing FTA utilization, this study develops a conceptual model from the perspective of the adoption of information technology innovations. Eight factors derived from the TOE framework are proposed to explore the determinants of FTA utilization in export. Partial least squares structural equation modeling is employed to analyze the data collected from 162 exporting small- and medium-sized enterprises in the South Korean textile industry. The findings reveal that compatibility and trading partner influence are positively associated with FTA utilization, while complexity is negatively related. Factors of organizational context do not show any relationship with FTA utilization. This study is the first to theoretically analyze and empirically test the determinants of FTA utilization from the perspective of technological innovation adoptions. By examining the relative importance of TOE factors in the utilization of FTA schemes, this study expects to advance a holistic understanding on the perceived factors that could potentially affect the utilization of FTA schemes.
Keywords: F14; F15; M16; 330; Free Trade Agreement; FTA Utilization; Technology–Organization–Environment Framework; Small- and Medium-sized Enterprises